The Impacts of Multi-environmental Constructs on Tourism Destination Competitiveness: Local Residents’ Perceptions - Chin, Chee-Hua; Lo, May-Chiun; Abang Azlan, Mohamad; Vikneswaran, Nair (Canadian Center of Science and Education, 2017)
In the rural tourism industry, the environment has emerged to be of most concern to the local communities, followed by social-cultural and economic issues. Stemming from the awareness, the environment has become one of the main pillars for sustainable tourism development, particularly, rural tourism destination. On the other note, in a competitive tourism market, it is important for rural tourism destinations to create competitive advantage in order to attract visitors. Therefore, competitiveness theory underpins the research framework proposed and attempts to examine the impacts of multi-environmental constructs towards the development of rural tourism destination competitiveness. A total of 278 respondents comprising of local communities from rural destinations in Sarawak, Malaysia took part voluntarily in this study. To assess the developed model, SmartPLS 2.0 (M3) is applied based on path modelling and bootstrapping. The findings showed that local residents are in their believed that for a rural tourism destination to enhance its competitiveness, environmental education is the key to increase environmental conservation that lead to better quality of environment. Tourism infrastructure is an added advantage to increase a tourism destination competitiveness. This study further discussed on the implications of the findings, limitations, and direction for future research.